2016
DOI: 10.2147/copd.s108813
|View full text |Cite
|
Sign up to set email alerts
|

Obesity might be a good prognosis factor for COPD patients using domiciliary noninvasive mechanical ventilation

Abstract: Cachexia is known to be a deteriorating factor for survival of patients with chronic obstructive pulmonary disease (COPD), but data related to obesity are limited. We observed that obese patients with COPD prescribed long-term noninvasive mechanical ventilation (NIMV) had better survival rate compared to nonobese patients. Therefore, we conducted a retrospective observational cohort study. Archives of Thoracic Diseases Training Hospital were sought between 2008 and 2013. All the subjects were prescribed domici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In PULM disease, we confirm previously described associations between improved survival and younger age 10 , 11 and obesity. 25 , 26 In COPD, cachexia is associated with systemic inflammation, adverse metabolic changes and reduced survival. 27 29 An unexpected new association of oxygen therapy and improved survival in the PULM group in our study probably reflects a Western Australian policy of prohibiting oxygen therapy prescription to current smokers.…”
Section: Discussionmentioning
confidence: 99%
“…In PULM disease, we confirm previously described associations between improved survival and younger age 10 , 11 and obesity. 25 , 26 In COPD, cachexia is associated with systemic inflammation, adverse metabolic changes and reduced survival. 27 29 An unexpected new association of oxygen therapy and improved survival in the PULM group in our study probably reflects a Western Australian policy of prohibiting oxygen therapy prescription to current smokers.…”
Section: Discussionmentioning
confidence: 99%
“…In our data set, COPD hospitalizations with DM were relatively younger and might have a higher body mass index than the COPD patients with no diabetes. Several studies have shown that underweight patients had a higher mortality than COPD patients with normal BMI, whereas overweight and obese individuals were associated with lower mortality [ 38 , 39 , 40 , 41 , 42 ]. In our study, we found that obesity was more common in diabetic patients with complications, and they had lower odds of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for this is unclear but is likely to be related to the obesity paradox observed in critical care patients (42,43). Although this was previously seen only in patients requiring invasive mechanical ventilation (44,45), it has now been demonstrated in patients who also require NIV (40).…”
Section: Niv In Chronic Hypercapnic Respiratory Failurementioning
confidence: 99%
“…Obesity appears to be a protective factor in this patient group. Patients receiving domiciliary NIV with a BMI >30 kg/m 2 had longer survival compared with those with a BMI 20-30 kg/m 2 (40,41). It is recognised that obstructive sleep apnoea (OSA) is a common feature in obese patients, and so this protective effect could be due to the effect of NIV of improving the OSA; however even with adjustment for OSA, obesity appeared to have a protective effect (41).…”
Section: Niv In Chronic Hypercapnic Respiratory Failurementioning
confidence: 99%